PENINGKATAN MOTIVASI BELAJAR IPA MELALUI IMPLEMENTASI METODE INQUIRY SISWA KELAS V SEKOLAH DASAR - Mahlianurrahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the low motivation of students in grade V SD Negeri Pasi Pinang. This study aims to describe the effort to improve students' learning motivation through the use of inquiry methods and to increase learning motivation through the use of inquiry method in science subjects. The type of this research is classroom action research, the subject of this research is the students of class V SD Negeri Pasi Pinang which amounted to 24 students. The object of this research is the improvement of students' learning motivation in science subjects. The results showed that the use of inquiry method can improve the motivation of students in grade V SD Negeri Pasi Pinang. This can be seen from the average score of students' learning motivation in cycle I is 60.2%, in cycle II increases with score 70.5%, and cycle III increases with score 92.8%. based on the results of these studies indicate that the student's learning motivation every cycle has increased after applied inquiry method.